(untitled) (Revista Española de Fisiología, 1969)
Lipase Activity of Severa! Tissues from Normal and Pancreatectomized Dogs A study concerning the blood, fat, muscle, heart, liver and intestine lipolitic activity of normal and pancreatectomized dogs has been carried out. Under normal conditions the lipolitic activity in fat and intestine is high, meanwhile in the rest of tissues the valúes are low. After the removal of páncreas it was observed a decrease of lipolitic activity in all analysis taken 6, 12 and 18 hours after the operation. On the other hand, between the 24 on 72 hours an increase of lipase is produced, mainly in fat and intestine where a normal level is nearly reached. In the liver the valúes reached three times the normal level, and in the heart also reaches a high level.